2017
DOI: 10.1002/pssa.201700309
|View full text |Cite
|
Sign up to set email alerts
|

Theory of a carbon‐oxygen‐hydrogen recombination center in n‐type Si

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.We have recently found that in-diffusion of hydrogen into n-type Si crystals containing oxygen and carbon impurities can result in the formation of powerful recombination centers (M. Vaqueiro-Contreras et al., to appear in PSS RRL). Here, we describe a combination of first-principles calculations and electrical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the literature, while hydrogenation has been proven to be effective in improving the performance of solar cells, , hydrogen has been shown to cause recombination in multiple ways, such as formation of structural defects or platelets, , deactivation of phosphorus dopants, formation of powerful recombination centers composed of carbon, oxygen, and hydrogen, , and creation of vacancy-hydrogen complexes . It was also suggested that hydrogen itself could cause recombination, potentially resulting in a reduction in the carrier lifetime, which might also be a possible explanation for the impact of excess hydrogen observed herein.…”
Section: Resultsmentioning
confidence: 67%
“…In the literature, while hydrogenation has been proven to be effective in improving the performance of solar cells, , hydrogen has been shown to cause recombination in multiple ways, such as formation of structural defects or platelets, , deactivation of phosphorus dopants, formation of powerful recombination centers composed of carbon, oxygen, and hydrogen, , and creation of vacancy-hydrogen complexes . It was also suggested that hydrogen itself could cause recombination, potentially resulting in a reduction in the carrier lifetime, which might also be a possible explanation for the impact of excess hydrogen observed herein.…”
Section: Resultsmentioning
confidence: 67%
“…DLTS and MCTS spectra recorded on a sample from n-type Cz silicon containing oxygen-related thermal double donors (E 4 trap) with a high concentration and C-O-H defects (E 1 /H 1 and E 2 /H 2 traps). 38,39 The spectra were recorded with a rate window corresponding to e = 50 s 38,39 It appears that there is a small population of majority carriers in the depletion region during the MCTS experiment as can be seen from the majority carrier peak in the low temperature region. This peak is due to the second donor level of oxygen-related thermal double donors having a large electron capture cross section.…”
Section: Minority Carrier Processes and Carrier Capture Measurementsmentioning
confidence: 99%
“…11 The possible structures of the C-O-H complex with electronic properties close to those for the H 1 and H 2 traps have been found from the first principles calculations. 11,17 Here, we present results of a study of the electronic properties and thermal stability of the E 1 , E 2, and E 4 electron traps and some results on the relation of these traps to the most abundant oxygen, carbon, and hydrogen impurities. It should be noted, however, that the E 1 -E 4 traps do not appear to be the significant recombination centers for holes in n-type Si crystals because of the closeness of their energy levels to the conduction band edge.…”
Section: A Effect Of Hydrogenation Treatments On Minority Carrier Lifetime In N-type Cz-simentioning
confidence: 99%